Post-hoc comparison of vitamin D status at three timepoints during pregnancy demonstrates lower risk of preterm birth with higher vitamin D closer to delivery. Issue 148 (April 2015) - Wagner, C.L.; Baggerly, C.; McDonnell, S.L.; Baggerly, L.; Hamilton, S.A.; Winkler, J.; Warner, G.; Rodriguez, C.; Shary, J.R.; Smith, P.G.; Hollis, B.W.
Highlights: Association between serum 25(OH)D and preterm birth during 3 timepoints was examined. 25(OH)D value closest to delivery more strongly correlated with preterm birth. Findings most notable in Hispanic women. 47% lower preterm birth rate associated with 25(OH)D >100 nmol/L at 27 weeks. Later intervention as rescue therapy may positively impact risk of preterm delivery. Abstract: There have been observational reports that maternal vitamin D status at baseline and not closest to delivery is a better predictor of pregnancy outcomes, suggesting that a cascade of events is set into motion that is not modifiable by vitamin D supplementation during later pregnancy. To address this issue, in this exploratory post-hoc analysis using correlation and logistic regression, we sought to measure the strength of the association between serum 25(OH)D concentrations at 3 timepoints during pregnancy: baseline, 1st trimester (<16 weeks); 2nd trimester (16–26 weeks); and 3rd trimester (≥ 27 weeks) and preterm birth. It was hypothesized that the 25(OH)D value closest to delivery would be most significantly associated with preterm birth. To accomplish this objective, the datasets from NICHD ( n  = 333) and Thrasher Research Fund ( n  = 154) vitamin D supplementation pregnancy studies were combined. The results of this analysis were that 25(OH)D values closer to delivery were more strongly correlated with gestational age at delivery than earlier values: 1st trimester: r  = 0.11 ( p  = 0.02); 2nd trimester: r  = 0.08 ( p  = 0.09); and 3rd trimester: r  = 0.15 ( p  = 0.001). When logistic regression was performed with preterm birth (<37 weeks) as the outcome and 25(OH)D quartiles as the predictor variable, adjusting for study and participant race/ethnicity, as with the correlation analysis, the measurements closer to delivery were more significantly associated and had a higher magnitude of effect. That is, at baseline, those who had serum concentrations <50 nmol/L (20 ng/mL) had 3.3 times of odds of a preterm birth compared to those with serum concentrations ≥100 nmol/L (40 ng/mL; p  = 0.27). At 2nd trimester, the odds were 2.0 fold ( p  = 0.21) and at the end of pregnancy, the odds were 3.8 fold ( p  = 0.01). The major findings from this exploratory analysis were: (1) maternal vitamin D status closest to delivery date was more significantly associated with preterm birth, suggesting that later intervention as a rescue treatment may positively impact the risk of preterm delivery, and (2) a serum concentration of 100 nmol/L (40 ng/mL) in the 3rd trimester was associated with a 47% reduction in preterm births. This article is part of a Special Issue entitled '17th Vitamin D Workshop'.